Effect of supplementation with gold button silo (Tithonia diversifolia) in fattening sheep grazing Brachiaria spp (Revista Sistemas de Producción Agroecológicos, 2014)
Tithonia diversilia is an acceptable adequate forage plant for feeding ruminants (cattle, goats, sheep and buffaloes), with good level of protein (18.9 to 28.8), high degradability in the rumen, and low fiber levels of anti-nutritional substances such as phenols and tannins, based on the above, the following research, Villavicencio, Meta, Colombia is performed. The main objective is to determine the effect of supplementation with silo (Tithonia diversifolia) in the diet of sheep for fattening, using different dry matter percentages: 0%, 0.5%, 0.75% and 1% from the live animal, assessing weight gain, feed conversion, feed efficiency and consumption of forage fed Brachiaria spp main power supply sheep. 12 weaned sheep were used with an average weight 19.4 kg the randomly distributed into 4 groups naming treatments as follows: T1: control group, unsupplemented animals; T2, T3 and T4 sheep supplemented with Tithonia diversilia silo levels: 0.5%, 0.75 and 1%, respectively. The total weight gain was lower (P
Keywords: Tithonia diversifolia; feeding; crossbred sheep; camuros; silage